Angiotensin Converting Enzyme‐2 Therapy Improves Liver Fibrosis and Glycemic Control in Diabetic Mice With Fatty Liver. Issue 5 (23rd December 2021) - Rajapaksha, Indu G.; Gunarathne, Lakmie S.; Asadi, Khashayar; Laybutt, Ross; Andrikopoulous, Sof; Alexander, Ian E.; Watt, Mathew J.; Angus, Peter W.; Herath, Chandana B.
Abstract : Nonalcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease and is frequently associated with type 2 diabetes. However, there is no specific medical therapy to treat this condition. Angiotensin‐converting enzyme 2 (ACE2) of the protective renin angiotensin system generates the antifibrotic peptide angiotensin‐(1‐7) from profibrotic angiotensin II peptide. In this study, we investigated the therapeutic potential of ACE2 in diabetic NAFLD mice fed a high‐fat (20%), high‐cholesterol (2%) diet for 40 weeks. Mice were given a single intraperitoneal injection of ACE2 using an adeno‐associated viral vector at 30 weeks of high‐fat, high‐cholesterol diet (15 weeks after induction of diabetes) and sacrificed 10 weeks later. ACE2 significantly reduced liver injury and fibrosis in diabetic NAFLD mice compared with the control vector injected mice. This was accompanied by reductions in proinflammatory cytokine expressions, hepatic stellate cell activation, and collagen 1 expression. Moreover, ACE2 therapy significantly increased islet numbers, leading to an increased insulin protein content in β‐cells and plasma insulin levels with subsequent reduction in plasma glucose levels compared with controls. Conclusion: We conclude that ACE2 gene therapy reduces liver fibrosis and hyperglycemia in diabetic NAFLD mice and has potential as a therapy for patients with NAFLD with diabetes.